Modern Galician poetry. A family portrait - Nogueira Pereira, María Xesús (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This paper gives an overview of modern Galician poetry, focused on main tendencies, tensions and authors. The study goes back to the discourse recuperation process carried out during the post-war period. In this sense, information is given on the coexistence of different proposals and generations during that period. This paper also deals with the poetic renewal process in the eighties, which definitely overcame the dominating social realist discourse and promoted culturalist poetry to the detriment of other proposals. Finally, tendencies in the first years of the nineties are discussed. This helps us to understand the actual situation characterized to a certain extent by the cohabitation of different generations.